2019
DOI: 10.1002/advs.201801521
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Topography Regulates Synaptic Transmission at the Neuromuscular Junction

Abstract: Recreation of a muscle that can be controlled by the nervous system would provide a major breakthrough for treatments of injury and diseases. However, the underlying basis of how neuron–muscle interfaces are formed is still not understood sufficiently. Here, it is hypothesized that substrate topography regulates neural innervation and synaptic transmission by mediating the cross‐talk between neurons and muscles. This hypothesis is examined by differentiating neural stem cells on the myotubes, formed on the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
1
33
1
Order By: Relevance
“…glutamate stimulation) caused the observed changes in muscle fiber calcium transients and muscle fiber contractions, we studied the effect of BOTOX (BOT, presynaptic blocker) and d-tubocurarine (DTC, post synaptic blocker) treatments in our system. Our studies revealed a significant decrease in calcium transient activity and an absence of tissue contraction in response to glutamate stimulation if neuromuscular co-cultures were pre-treated with BOTOX or d-tubocurarine (Figure 3D and Video 7) doses reported by others to fully block activity (Ko et al, 2019; Madden et al, 2015).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…glutamate stimulation) caused the observed changes in muscle fiber calcium transients and muscle fiber contractions, we studied the effect of BOTOX (BOT, presynaptic blocker) and d-tubocurarine (DTC, post synaptic blocker) treatments in our system. Our studies revealed a significant decrease in calcium transient activity and an absence of tissue contraction in response to glutamate stimulation if neuromuscular co-cultures were pre-treated with BOTOX or d-tubocurarine (Figure 3D and Video 7) doses reported by others to fully block activity (Ko et al, 2019; Madden et al, 2015).…”
Section: Resultssupporting
confidence: 63%
“…However, it should be noted that single fiber level analyses may be easier to perform in a 2D culture setting. As such, we expect that focusing efforts on modifying 2D cultures to control the microenvironment in ways that can accommodate myofiber contractility and alignment, might result in the formation of functional NMJs in vitro at earlier time-points, as was recently demonstrated in work with rodent myoblasts and neural cells (Ko et al, 2019). If successful, it is feasible to imagine de novo AChR subunit switching in 2D neuromuscular cultures as well.…”
Section: Discussionmentioning
confidence: 93%
“…[ 144 ] As MNs attach to myofibers, they form NMJs, which have been successfully formed in 3D coculture experiments in vitro and subsequently used to stimulate myofibers both chemically and electrically. [ 98,145 ] Unfortunately, these methods of stimulation frequently result in phenotypically immature myofibers, as the neural networks formed between MNs and myoblasts do not provide enough stimulation to promote mature myogenic differentiation. [ 146 ] Bakooshli et al.…”
Section: External Stimulatorsmentioning
confidence: 99%
“…Since the promotion of alignment is such a crucial aspect in mechanical stimulation studies, researchers have used micro‐grooved substrates to promote the alignment of various myoblast cocultures. [ 2,145,154 ] Ko et al. [ 145 ] advanced neural and muscle cocultures by plating primary myoblasts and neural stem cells together onto a micro‐grooved poly(urethane acrylate) (PLA) substrate, which was coated with Matrigel to promote cell attachment, shown in Figure .…”
Section: External Stimulatorsmentioning
confidence: 99%
See 1 more Smart Citation